1999
DOI: 10.1056/nejm199901213400302
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Superovulation and Intrauterine Insemination in the Treatment of Infertility

Abstract: Among infertile couples, treatment with induction of superovulation and intrauterine insemination is three times as likely to result in pregnancy as is intracervical insemination and twice as likely to result in pregnancy as is treatment with either superovulation and intracervical insemination or intrauterine insemination alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
226
5
13

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(261 citation statements)
references
References 10 publications
17
226
5
13
Order By: Relevance
“…In theory the probability of conception can be further improved by increasing the number of available oocytes at the site of fertilization, hence the role of COH. Controlled ovarian hyper-stimulation in combination with intrauterine insemination has been shown to result in significantly higher pregnancy rate when compared to un-stimulated (natural cycle) IUI [1,5]. Our data is consistent with these studies, but only among younger women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In theory the probability of conception can be further improved by increasing the number of available oocytes at the site of fertilization, hence the role of COH. Controlled ovarian hyper-stimulation in combination with intrauterine insemination has been shown to result in significantly higher pregnancy rate when compared to un-stimulated (natural cycle) IUI [1,5]. Our data is consistent with these studies, but only among younger women.…”
Section: Discussionsupporting
confidence: 91%
“…Controlled ovarian hyper-stimulation (COH) in combination with intrauterine insemination (IUI) has been shown to result in significantly higher pregnancy rate compared to unstimulated (natural cycle) IUI [1]. However a meta-analysis of 4 trials including 479 completed cycles found no significant difference between IUI in cycles with COH and IUI in natural cycle [2].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of intrauterine insemination to exogenous gonadotropin treatment has been shown to increase the efficacy of infertility treatment in patients with unexplained and male factor infertility (25)(26)(27). Conceivably, following gonadotropin administration, IUI can be considered for women with HH.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this finding, IUI has been traditionally performed around post-hCG 36th hour. Guzick et al have reported 33% pregnancy rate when IUI was performed between 36-40 h after hCG injection [5]. Two hCG-IUI intervals, 33 versus 39 h, was compared in a prospective, randomised clinical trial [6].…”
Section: Discussionmentioning
confidence: 99%